Pengaruh Model Pembelajaran Kooperatif Tipe Think, Talk, Write (TTW) Berbantuan Media Pop-Up Book terhadap Kemampuan Komunikasi Matematis Siswa Kelas IV pada Materi Pecahan di SDN 1 Sokong - Bintang Narayana; Radiusman; Nurkhaerat Alimuddin (Mataram University, 2026)
This study aimed to determine the effect of the Think, Talk, Write (TTW) cooperative learning model assisted by Pop-Up Book media on fourth-grade students' mathematical communication skills in fraction material at SDN 1 Sokong. This research employed a quantitative approach with a quasi-experimental design using a Pretest–Posttest Control Group Design. The sample consisted of 62 students divided into an experimental class (IV A, n=32) and a control class (IV B, n=30). The research instrument was an essay test measuring three indicators of mathematical communication: (1) writing ideas in mathematical sentences, (2) selecting concepts for problem solving, and (3) formulating mathematical models. Data were analyzed using normality tests (Kolmogorov-Smirnov), homogeneity tests (Levene's Test), and Independent Sample t-test through SPSS. Results showed a significant effect of the TTW model assisted by Pop-Up Book on students' mathematical communication skills (Sig. 2-tailed = 0.000 < 0.05). The experimental class achieved a post-test mean of 81.25, significantly higher than the control class mean of 63.44. Effect size analysis yielded Cohen's d = 2.31, indicating a very large practical effect. Previous studies have generally examined the effectiveness of TTW or Pop-Up Book separately; however, their integration for improving mathematical communication skills in fraction material at the elementary school level has rarely been investigated. These findings indicate that the integration of TTW with Pop-Up Book media is effective in enhancing mathematical communication skills in fraction material.